EFFECTS OF NEUTRALIZATION PERIOD AND TEMPERATURE IN ALKALI REFINING ON THE QUALITY OF SARDINE OIL - Hari Eko lrianto; Sri Ningrum Pudjiastuti; Pipih Suptijah (Research Center for Fisheries, 1995)
Most fish meal weste oil encountered in Indonesia has high free fatty acid (FFA)value, dark colour end strong fishy odour. Thus, the oil needs refining process for thequality improvement before-further uses, such as by alkali refining application.